Analisis Penggunaan Infografis Mengenai Masalah Pelestarian Sumber Daya Alam Sebagai Upaya Meningkatkan Literasi Lingkungan Pada Siswa Sekolah Dasar - Farina Trias Alwasi; Widianti Nurohmah; Prihantini Prihantini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The lack of human awareness of environmental problems and limited natural resources is a challenge that needs to be corrected for the survival of future generations. Raising awareness through environmental literacy habits needs to be instilled from basic education, this is done because instilling character values will be more effective given from an early age. Infographic media is a way to convey overall information clearly, complexly and quickly. With the aim of knowing the use of infographics regarding the problem of preserving natural resources as an effort to increase environmental literacy in elementary school students. The type of research used is a qualitative approach with a literature study method. Infographics are an interesting medium for increasing environmental literacy in students. Students can be guided to collect and analyze problems in the surrounding environment, analyze the impacts that will occur, and find solutions to overcome these problems which are outlined in the form of infographics. By instilling environmental literacy in children from an early age, it is possible for students to have an attitude of caring about the environment.